Meningkatkan Motorik Halus Anak Melalui Kegiatan Menjiplak Dengan Media Alam Di Paud Bintang Cemerlang - Nelis Hayati; Asnawati Asnawati; Ranny Fitria Imran (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to enhance the fine motor skills of children at PAUD Bintang Cemerlang through tracing activities using natural materials. The study employed the Classroom Action Research (CAR) method, conducted over two cycles; each cycle consisted of planning, action implementation, observation, and reflection stages. The research subjects comprised 12 children. Data collection was carried out through observation and documentation. Data analysis was performed using descriptive quantitative methods, utilizing percentages to track the development of the children's fine motor skills. The results indicate that tracing activities using natural materials can improve the fine motor skills of early childhood learners. This improvement was evident across each learning cycle. In Cycle I, Meeting 1, the children's fine motor skills achieved a score of 40.41% (categorized as